2019
DOI: 10.3758/s13421-019-00949-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the implicit acquisition of nonadjacent transitional probabilities by ERPs

Abstract: The implicit acquisition of complex probabilistic regularities has been found to be crucial in numerous automatized cognitive abilities, including language processing and associative learning. However, it has not been completely elucidated how the implicit extraction of second-order nonadjacent transitional probabilities is reflected by neurophysiological processes. Therefore, this study investigated the sensitivity of event-related brain potentials (ERPs) to these probabilistic regularities embedded in a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 100 publications
(179 reference statements)
8
57
1
Order By: Relevance
“…Thus, it is not surprising that recent studies have been using online (neural) and not only post-learning offline measures of SL (e.g., 2-AFC) to study the processes and mechanisms that underlie the extraction of the statistical regularities embedded in the input and also to shed light on other controversial issues largely unexplored in the SL literature, as the nature of representations that arise from SL tasks (e.g., Batterink et al, 2015a , 2019 ; Batterink and Paller, 2017 ; Batterink et al, 2019 ; Kóbor et al, 2018 , 2019 ; Batterink, 2020 ; Horváth et al, 2020 ; see Batterink et al, 2019 ; and Daltrozzo and Conway, 2014 for recent reviews). This strongly contrasts with what has been investigated in the related implicit learning field (see Perruchet and Pacton, 2006 , and also Christiansen, 2019 ) where a significant amount of research has been devoted to examining the type of representations and the (implicit vs. explicit) nature of the knowledge emerging from tasks such as the artificial grammar learning (AGL) task (Reber, 1967 ) or the serial reaction time (SRT) task (Nissen and Bullemer, 1987 ) or any version of it, either using subjective confidence scales [see for instance Jiménez et al, 2020 or Soares (under review) for recent examples] or dissociating these two types of knowledge through the manipulation of the instructions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not surprising that recent studies have been using online (neural) and not only post-learning offline measures of SL (e.g., 2-AFC) to study the processes and mechanisms that underlie the extraction of the statistical regularities embedded in the input and also to shed light on other controversial issues largely unexplored in the SL literature, as the nature of representations that arise from SL tasks (e.g., Batterink et al, 2015a , 2019 ; Batterink and Paller, 2017 ; Batterink et al, 2019 ; Kóbor et al, 2018 , 2019 ; Batterink, 2020 ; Horváth et al, 2020 ; see Batterink et al, 2019 ; and Daltrozzo and Conway, 2014 for recent reviews). This strongly contrasts with what has been investigated in the related implicit learning field (see Perruchet and Pacton, 2006 , and also Christiansen, 2019 ) where a significant amount of research has been devoted to examining the type of representations and the (implicit vs. explicit) nature of the knowledge emerging from tasks such as the artificial grammar learning (AGL) task (Reber, 1967 ) or the serial reaction time (SRT) task (Nissen and Bullemer, 1987 ) or any version of it, either using subjective confidence scales [see for instance Jiménez et al, 2020 or Soares (under review) for recent examples] or dissociating these two types of knowledge through the manipulation of the instructions.…”
Section: Introductionmentioning
confidence: 99%
“…In the SL literature, the few studies conducted so far on the type of representations emerging from sequential learning tasks either in the auditory or visuomotor modality suggest that both implicit and explicit representations might arise from SL tasks (e.g., Turk-Browne et al, 2009 , 2010 ; Franco et al, 2011 ; Bertels et al, 2012 , 2015 ; Batterink et al, 2015a , b ; Kóbor et al, 2018 , 2019 ; Horváth et al, 2020 ). For instance, Batterink et al ( 2015a ) recorded behavioral (RTs/accuracy) and ERP responses while participants performed two post-learning tasks: a speeded target detection task, aimed to assess SL indirectly as it asks participants to detect as fast and accurately as possible a specific syllable within a continuous speech stream, and the abovementioned 2-AFC task combined with a remember/know procedure to assess SL directly under either implicit or explicit conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported such result, even using self-paced timing (Nemeth, Janacsek, & Fiser, 2013;Song et al, 2008); the underlying process, however, is still unclear (cf. Kóbor et al, 2019). Better performance on highfrequency random trials may suggest that statistical learning is primary compared to sequence learning.…”
Section: Sequence Learning and Consolidationmentioning
confidence: 99%
“…Consolidation refers to the changes in the acquired knowledge during the post-learning offline periods (Krakauer & Shadmehr, 2006;Meier & Cock, 2014;Robertson, 2009;Robertson, Pascual-Leone, & Miall, 2004). Typically, incidentally acquired (statistical 5 or sequence) knowledge is retained during the offline period (Hallgató, Győri-Dani, Pekár, Janacsek, & Nemeth, 2013;Janacsek & Nemeth, 2012;Kim, Seitz, Feenstra, & Shams, 2009;Kóbor et al, 2019;Rickard et al, 2008;Song, Howard, & Howard, 2007b). In contrast, previous studies on intentionally acquired sequence knowledge led to mixed findings: while in some cases successful consolidation of the acquired knowledge means lower degree of forgetting (Mednick, Cai, Kanady, & Drummond, 2008), in other cases retention or even improvement in performance can occur after the delay period (Pan & Rickard, 2015;Robertson, Pascual-Leone, & Miall, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While statistical learning occurs in a rapid manner and reaches its plateau quickly, learning of sequential rules is characterized by a gradual change (Kóbor et al, 2018;Simor et al, 2019). Despite the growing interest in these simultaneous learning mechanisms (Conway, 2020), the neurophysiological processes behind them remain largely unknown (Kóbor et al, 2019(Kóbor et al, , 2018 and it is an open question how these parallel learning mechanisms are coded at the neurophysiological level. However, solving this puzzle represents a methodological challenge.…”
Section: Introductionmentioning
confidence: 99%